Knowledge and Attitude regarding Patient Safety among Undergraduate Nursing Students - Chhetri, Rejina; Ghimire, Babita; Upadhyay, Hari Prasad (Journal of Bharatpur Hospital, 2026)
BackgroundPatient safety as the absence of preventable harm to a patient while providing health care with the reduction of unnecessary harm associated with better health care. It is crucial to evaluate nursing students' knowledge and attitudes toward patient safety to encourage students in patient safety activities. So, this study was carried out to assess the knowledge and attitude regarding patient safety among undergraduate nursing students.MethodsA cross-sectional analytical study was conducted to assess the knowledge and attitude regarding patient safety among undergraduate nursing students. Total enumerative sampling technique was used to obtain a sample of 131 undergraduate nursing students. The data was collected by using semi-structured self-administered questionnaire, ethical approval was obtained (20240210-02) and analyzed in the statistical package for social science with descriptive statistics (frequency, percent, mean, standard deviation) and inferential statistics (chi-square). ResultsThis study showed 48.1% had poor knowledge and only 48.1% of the respondents had positive attitude. There is statistically significance association between level of knowledge regarding patient safety and age (p-value 0.001), educational level (p-value 0.001), experience of clinical practice (p-value 0.001) and statistically significance association between level of attitude regarding patient safety and age (p-value 0.029). ConclusionsAbout half of the respondents had poor knowledge regarding patient safety and more than half of the respondents had negative attitude. On the basis of findings, still need to do more focus on the concepts and skills on patient safety among nursing students. First, students’ needs to be taught about patient safety along with demonstration in college and before they are exposed for clinical experience.